“We Need to be Better”: Race, Outdoor Recreation, and Corporate Social Advocacy - Tarin, Carlos Anthony; Upton, Sarah De Los Santos; Hernández, Leandra Hinojosa (Frontiers in Communication, 2021)
The summer 2020 protests following the killings of George Floyd, Breonna Taylor, Ahmaud Arbery, and others sparked important conversations about race, police brutality, and institutionalized racism in the United States. In response to widespread civil unrest, organizations across the country issued statements condemning anti-Black violence and in support of the Black Lives Matter movement. This essay analyzes the public statements released by 50 outdoor sport and recreation organizations. Extending literature on race and corporate social advocacy, we develop the concept of conciliatory discourse which functions by rhetorically constructing (1) a non-specification of grievance, (2) an obfuscation of commitments to action, and (3) a reinforcement of previous actions or processes. We argue that, while many organizations took action in support of racial justice, their public statements complicate long-term commitments for inclusivity and diversity.